2011
DOI: 10.1186/1471-2229-11-34
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of OsCYP2, a rice cyclophilin that confers salt tolerance in rice (Oryza sativa L.) seedlings when overexpressed

Abstract: BackgroundHigh Salinity is a major environmental stress influencing growth and development of rice. Comparative proteomic analysis of hybrid rice shoot proteins from Shanyou 10 seedlings, a salt-tolerant hybrid variety, and Liangyoupeijiu seedlings, a salt-sensitive hybrid variety, was performed to identify new components involved in salt-stress signaling.ResultsPhenotypic analysis of one protein that was upregulated during salt-induced stress, cyclophilin 2 (OsCYP2), indicated that OsCYP2 transgenic rice seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 29 publications
4
68
0
1
Order By: Relevance
“…We have found higher expression levels of a cyclophilin A (CypA) homologue in P. indica under salt-stress conditions (unpublished work). This observation is similar to the previously reported role of cyclophilin in conferring salt-stress tolerance in rice (Ruan et al, 2011). Cyclophilins are proteins that are widely distributed and abundantly found in eukaryotic and prokaryotic systems and are present in the cytosol as well as in the nucleus (Wang & Heitman, 2005).…”
Section: Introductionsupporting
confidence: 91%
“…We have found higher expression levels of a cyclophilin A (CypA) homologue in P. indica under salt-stress conditions (unpublished work). This observation is similar to the previously reported role of cyclophilin in conferring salt-stress tolerance in rice (Ruan et al, 2011). Cyclophilins are proteins that are widely distributed and abundantly found in eukaryotic and prokaryotic systems and are present in the cytosol as well as in the nucleus (Wang & Heitman, 2005).…”
Section: Introductionsupporting
confidence: 91%
“…This observation is similar to the previously reported role of cyclophilin in conferring salinity stress tolerance in rice. 50 Recently we have also reported the sequence-specific 1 H, 13 C and 15 N NMR assignments and preliminary X-ray crystallographic analysis of Cyclophilin A like protein from Piriformospora indica. 51,52 In case of the expression analysis under different developmental stages, the Arabidopsis cyclophilin genes exhibited higher response to the senescence conditions.…”
Section: Discussionmentioning
confidence: 92%
“…In recent past, several publications have reported that using the comparative transcriptomic approach between contrasting genotypes of rice (IR64 and Pokkali), several differentially regulated genes could be isolated, which then served as useful genes in functional genomic studies (Kumari et al 2009 ;Karan et al 2009 ;Mustafa et al 2010;Kumar et al 2012 ;Soda et al 2013 ). It is also true that the analysis of changes in proteome of crop plants in response to abiotic stresses can also be used as a starting point to fi sh out the genes, which may ultimately serve as the "candidate genes" (Ruan et al 2011 ) In this chapter, we have described the various "omics"-based approaches, which have been employed in recent years to understand the response of plants towards abiotic stresses. For brevity sake, we have restricted our discussion to the identifi cation of signaling molecules, which have been studied by employing the particular "omics" approach.…”
Section: Introductionmentioning
confidence: 98%